PENGARUH INTELLECTUAL CAPITAL TERHADAP PROFITABILITAS, PRODUKTIVITAS, DAN NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Devina Kusuma Wardani; Bambang Widarno; Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
The purpose of this study was to analyze the significance of the influence of intellectual capital on profitability, productivity and firm value in food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange. The population in this study were all food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange at the 2014-2017 period totaling 18 companies, the number of samples used in the study was 11 companies with the sampling technique using purposive sampling. The data analysis technique used is the classical assumption test, and simple linear regression analysis, t test, F test, and test coefficient of determination. The results of the study concluded that intellectual capital has a significant positive effect on profitability, intellectual capital has a significant positive effect on productivity, intellectual capital has a significant positive effect on firm value.